2022
DOI: 10.3390/foods11192950
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Inclusion of Microalgae Schizochytrium spp. on Ewes’ Milk Quality and Oxidative Status

Abstract: An unprecedented challenge for nutritionists arises during the 21st century in order to produce highly nutritious and functional food which promotes human health. Polyunsaturated fatty acids (PUFA) that are highly contained in microalgae have broadly been confirmed for preventing cardiovascular diseases and regulating immune-oxidative status. However, their optimum dietary inclusion level needs to be defined since PUFA are prone to oxidation. For this purpose, 24 cross-bred dairy ewes, were separated into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…They found that a marine algae enriched diet elevated DHA concentration in milk. Furthermore, similar findings have also been reported by Zisis et al [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…They found that a marine algae enriched diet elevated DHA concentration in milk. Furthermore, similar findings have also been reported by Zisis et al [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, although the transfer efficiency of EPA, DPA, and DHA is quite low in ruminants due to their biohydrogenation [94,140], another important biomolecule can be formed. In this context, dietary supplementation with Schizochytrium spp., rich in ω6-DPA and DHA, enriched ovine [141] and caprine [94,142] milk with DHA, ω6-DPA, and CLA resulting in a two-fold increase in total milk PUFA content. More specifically, microalgae-fed goats and sheep produced milk fortified with up to four-and six-fold increased proportions of CLA, respectively.…”
Section: The Effect Of Microalgae On Animal Product Qualitymentioning
confidence: 99%
“…in goats' diet impaired milk oxidative status through the accumulation of toxic aldehydes such as MDAs and protein oxidation products (PCs) [124,142]. Dairy sheep were found to be more prone to oxidation since MDAs in milk were increased even in the lowest supplementation level [141]. Nevertheless, Christodoulou et al (2022) [122] reported that Spirulina supplementation in dairy sheep diet significantly increased the activity of antioxidant enzymes, namely SOD, CAT, and GSH-Px, in milk and its total antioxidant capacity.…”
Section: The Effect Of Microalgae On Animal Product Qualitymentioning
confidence: 99%
“…In addition to the environmental concerns, there has also been increasing attention paid to improving the nutritional quality of ruminant-derived products, particularly milk and meat [3][4][5][6]. Modifying the biohydrogenation of polyunsaturated fatty acids (PUFA) within the rumen can lead to changes in the fatty acid composition of ruminant milk and meat.…”
Section: Introductionmentioning
confidence: 99%